الدراسة التجريبية لمختلف أنواع رمال البناء لمنطقة الوادي باستعمال الملاط - مصطفى, بن موسى; السعيد, رزيق; السعيد, شفاح (University of El-Oued, 2020)
"يتمحور موضوعنا حول دارسة خبرة ومقارنة مختلف أنواع الرمل البناء المستعمل ، في منطقة الوادي . أحصينا أربعة أنواع شائعة الاستخدام وهم رمل البعاج ورمل أعسيلة ، ورملي جامعة الأحمر والأصفر ، بعد قيامنا بدراسة الخصائص الفيزيائية لهذه الأنواع الأربعة ، حضرنا أربعة أنواع من الملاط ، من هذه الرمال بنوعين مختلفين من الأسمنت ( عادي والمقاوم للأملاح ) ، قمنا بحفظها في وسطين مختلفين ( ماء عادي وماء صاعد بمنطقة الوادي ) . لدراسة المقاومة الميكانيكية و الديمومة ، وقد بينت النتائج المتحصل عليها ، اختلافات واضحة بين أنواع الرمال المستعملة ، هناك المتقارب والمتباعد . وبصفة عامة تبين أن رمل البعاج هو المثالي والأحسن في ما بينهم ، ثم يليه رمل أعسيلة ،ثم رملي جامعة . وهذه صورة توضح مكان الحاجر ""Our topic revolves around a study of the experience and comparison of the different types of sand used in construction in the valley. We counted four commonly used types, which are baaj sand, honeycomb sand, and Al-Ahmar and Yellow University sand. After we studied the physical properties of these four types, we prepared four types of slurries, from these sands with two different types of cement (normal and salt-resistant), and we saved them in two different mediums ( Normal water and rising water in the valley area). To study mechanical resistance and durability, the results obtained showed clear differences between the types of sand used, there are convergent and divergent types. In general, it turns out that the baaj sand is the ideal and the best among them, then it is followed by honeycomb sand, then collective sand. And this is a picture showing the location of the stoner"
Matéreaux en génie civil مذكرة ماستر تخصص
Keywords: "رمل البناء ملاط الاسمنت الديمومة المياه الصاعدة المقاومة المكانكية "; "Construction sand Cement mortar Permanence The rising waters Mechanical resistance مزيد"